(2x-5)3=27
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
`=(3x-1)^2+2(2x-1)(2x+5)+(2x+5)^2-(2x-3)(4x^2+6x+9):(2x-3)`
`=(3x-1)^2+2(2x-1)(2x+5)+(2x+5)^2-(2x-3)(4x^2+6x+9):(2x-3)`
`=(3x-1+2x+5)^2-(4x^2+6x+9)`
`=(5x+4)^2-(4x^2+6x+9)`
`=25x^2+40x+16-4x^2-6x-9`
`=21x^2+34x+7`
Ta có: \(\left(3x-1\right)^2-2\left(1-3x\right)\left(2x+5\right)+\left(5+2x\right)^2-\left(8x^3-27\right):\left(2x-3\right)\)
\(=\left(3x-1+2x+5\right)^2-\left(4x^2+6x+9\right)\)
\(=\left(5x+4\right)^2-\left(4x^2+6x+9\right)\)
\(=25x^2+40x+16-4x^2-6x-9\)
\(=21x^2+34x+7\)
a) \(3\left(2x-5\right)+125=134\)
\(\Leftrightarrow3\left(2x-5\right)=9\)
\(\Leftrightarrow2x-5=3\)
\(\Leftrightarrow2x=8\Leftrightarrow x=4\)
b) \(\left(2x+5\right)+\left(2x+3\right)+\left(2x+1\right)=27\)
\(\Leftrightarrow6x+9=27\)
\(\Leftrightarrow6x=18\Leftrightarrow x=3\)
d) \(27\left(x-27\right)-27=0\)
\(\Leftrightarrow27\left(x-27\right)=27\)
\(\Leftrightarrow x-27=1\Leftrightarrow x=28\)
(2x+3/5)^3+8/27=0
(2x+3/5)^3=-8/27
=>(2x+3/5)^3=(-2/3)^3
=>2x+3/5=-2/3
=>2x=-2/3-3/5
=>2x=-19/15
=>x=-19/15:2
=>x=-19/30
Vậy x=-19/30
Nhớ like cho mình nha. Chúc bn học tốt
`@` `\text {Ans}`
`\downarrow`
`3)`
`(2x + 1) \div 9 - 104 \div 13 = 27^2 \div 3^5`
`\Rightarrow (2x + 1) \div 9 - 8 = (3^3)^2 \div 3^5`
`\Rightarrow (2x + 1) \div 9 - 8 = 3^6 \div 3^5`
`\Rightarrow (2x + 1) \div 9 - 8 = 3`
`\Rightarrow (2x + 1) \div 9 = 3 + 8`
`\Rightarrow (2x + 1) \div 9 = 11`
`\Rightarrow 2x + 1 = 11 . 9`
`\Rightarrow 2x + 1 = 99`
`\Rightarrow 2x = 99 - 1`
`\Rightarrow 2x = 98`
`\Rightarrow x = 98 \div 2`
`\Rightarrow x = 49`
Vậy, `x = 49.`
3) \(\left(2x+1\right):9-104:13=27^2:3^5\)
\(\left(2x+1\right):9-8=729:243\)
\(\left(2x+1\right):9-8=3\)
\(\left(2x+1\right):9=8+3\)
\(\left(2x+1\right):9=11\)
( 2x + 1) = 11.9
2x+1 = 99
2x = 99-1
2x = 98
x = 98 : 2
x = 49
(2x-5)3=27
(2x-5)3=33
=>2x-5=3
2x=3+5
2x=8
x=8:2
x=4
(2x-5)^3=3^3
2x-5=3
2x=3+5
2x=8
x=4